Cell-penetrating peptides containing 2, 5-diketopiperazine (DKP) scaffolds as shuttles for anti-cancer drugs: conformational studies and biological activity. Issue 42 (22nd April 2020) - Feni, Lucia; Jütten, Linda; Parente, Sara; Piarulli, Umberto; Neundorf, Ines; Diaz, Dolores
Abstract : Cargo-peptides approaching cellular membranes: influence of cyclization and stereochemistry on cellular translocation activity of a novel group of cell-penetrating peptides containing bifunctional diketopiperazine. Abstract : A series of linear and cyclic peptidomimetics composed of a cell-penetrating peptide and a non-natural, bifunctional 2, 5-diketopiperazine scaffold is reported. Conformational studies revealed well-defined helical structures in micellar medium for linear structures, while cyclic peptidomimetics were more flexible. Biological investigations showed higher membrane-activity of cyclic derivatives allowing their use as shuttles for anti-cancer drugs.